NILAI MORAL DALAM NOVEL KONSPIRASI ALAM SEMESTA KARYA FIERSA BESARI - Sakaria Sakaria; Andi Uswatul Hasanah (Universitas Negeri Makassar, 2022)
Analysis of Moral Values in the Novel Conspiracy of the Universe by Fiersa Besari. This study aims to describe: (1) the spiritual moral values contained in the novel Konspirasi Alam Semesta by Fiersa Besari; (2) personal moral values contained in the novel Konspirasi Alam Semesta by Fiersa Besari; and (3) social moral values contained in the novel Konspirasi Alam Semesta by Fiersa Besari. This research is a qualitative descriptive study that analyzes the moral values of both spiritual, personal, and social contained in the novel Di Tanah Lada by Fiersa Besari. The instrument used in this study was the researcher himself who was assisted by a work analysis table. The data of this research are all sentences and paragraphs containing spiritual, personal, and social moral values in the novel Konspirasi Alam Semesta by Fiersa Besari. Data collection techniques used are reading and note-taking techniques. The overall data obtained were analyzed in depth with interactive data analysis techniques consisting of data collection, data reduction, data presentation, and drawing conclusions. The results of data analysis show that: (1) The spiritual moral values contained in the novel Konspirasi Alam Semesta Karya Fiersa Besar consist of eleven data with the most frequently emphasized forms of behavior being gratitude and prayer; (2) The personal moral values contained in the novel Konspirasi Alam Semesta by Fiersa Besari are mostly found in the form of responsible behavior; (3) The social moral values contained in the novel Konspirasi Alam Semesta by Fiersa Besari are found not only moral values to fellow humans but also to the homeland.